Voting for Diversity? Political Attitudes and Formal Political Participation of Gay Men and Lesbian Women in Germany - Hunklinger, Michael (Momentum Quarterly, 2021)
This paper uses original data from the LGBTIQ* Election Survey 2017 to examine political attitudes (Gabriel 2009), as well as formal political participation (Ekman/ Amna 2012), on the individual level (voting) and on the collective level (membership of parties, trade unions, and NGOs) of gay and lesbian citizens in Germany. The paper bridges the gap between conventional political participation research and queer studies and adds to both strands of research. It shows that the majority of gay and lesbian voters who participated in the survey support a progressive agenda and therefore vote for and engage with progressive and left-wing parties, since they tend to be more inclusive of the LGBTIQ* community. The most important issues for their voting decision were discrimination and homophobia, as well as issues like migration and the environment. Regarding formal political participation on a collective level, gay men are more involved in political parties than lesbian women who are instead active in NGOs.x